2022
DOI: 10.1073/pnas.2202197119
|View full text |Cite
|
Sign up to set email alerts
|

Measuring dynamic media bias

Abstract: Ideological media bias is increasingly central to the study of politics. Yet, past literature often assumes that the ideological bias of any outlet, at least in the short term, is static and exogenous to the political process. We challenge this assumption. We use longitudinal data from the Stanford Cable News Analyzer (2010 to 2021), which reports the screen time of various political actors on cable news, and quantify the partisan leaning of those actors using their past campaign donation behavior. Using one i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Fourth, although our datasets cover different time periods (see Table A1), none of our datasets allow us to examine variation within days. 17 Kim, Lelkes and McCrain (2022) provide evidence suggesting this should not affect our conclusions too strongly: according to these authors' measure of news bias, in recent years, large differences in the ideological slant of coverage on Fox News versus CNN and MSNBC persist throughout the day's programming. Nevertheless, examining viewership differences at a more granular level, such as across different shows, is clearly an important priority for future work.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Fourth, although our datasets cover different time periods (see Table A1), none of our datasets allow us to examine variation within days. 17 Kim, Lelkes and McCrain (2022) provide evidence suggesting this should not affect our conclusions too strongly: according to these authors' measure of news bias, in recent years, large differences in the ideological slant of coverage on Fox News versus CNN and MSNBC persist throughout the day's programming. Nevertheless, examining viewership differences at a more granular level, such as across different shows, is clearly an important priority for future work.…”
Section: Discussionmentioning
confidence: 83%
“…and Muise et al into liberal cable news and (2) do not distinguish between what time of day people consume these networks Kim, Lelkes and McCrain (2022). provide evidence consistent with both these choices: according to these authors' measure of news bias, in recent years both CNN and MSNBC's coverage has been similarly liberal (with MSNBC only slightly more liberal than CNN); and, although prime time shows have become even more biased in recent years, large differences in the ideological slant of coverage on Fox News versus CNN and MSNBC persist throughout the day's programming.…”
mentioning
confidence: 99%
“…Past work has been somewhat conflicted. Kim et al (2022) find that cable news polarizes with most of this done by primetime appearances. Yet other work has shown that when polarization is covered in the media, it turns the electorate moderates (M. Levendusky & Malhotra, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Past work has been somewhat conflicted. Kim et al (2022) find that cable news polarizes with most of this done by primetime appearances.…”
Section: Election Timing and Fundraisingmentioning
confidence: 99%
“…This claim, however, is difficult to empirically verify because the content on FNC is both a cause and an effect of consumer demand (Levin et al, 2023). As a result, if the content of media like FNC reflects existing consumer demand for programming that invokes fear, anxiety, and outrage (Gentzkow and Shapiro, 2010;Kim, Lelkes and McCrain, 2022), we cannot infer from content alone that real-world events that feel threatening would increase demand for conservative partisan media, especially among those who are not already high consumers. Since it is precisely these 1 Since we are only examining conservative partisan media in this study, we use the term, "conservative media", in order to distinguish it from the general term, "partisan media" (Levendusky, 2013).…”
Section: Introductionmentioning
confidence: 99%